The importance of small scales to the fruit-feeding butterfly assemblages in a fragmented landscape - Ribeiro, Danilo Bandini; Batista, Rômulo; Prado, Paulo I. [UNESP]; Brown Jr., Keith S.; Freitas, A. V.L. (Springer Nature, 2012)
Nowadays 37% of Earth's ice-free land is composed by fragments of natural habitats settled in anthropogenic biomes. Therefore, we have to improve our knowledge about distribution of organisms in remnants and to understand how the matrix affects these distributions. In this way, the present study aims to describe the structure of the butterfly assemblages and determined how richness and abundance are influenced by the scale of the surrounding vegetation. General linear models were used to investigate how the type and scale of vegetation cover within a radius of 100-2,000 m around the sampling point explained butterfly diversity. After sampling ten forest fragments we found 6,488 individuals of 73 species. For all clades tested null models explain the species richness at the fragments better than other models when we include the effect of butterfly abundance as a covariate. Abundance of Satyrini, Brassolini, and Biblidinae were best predicted by small scales (100-200 m), and large scales were more suited for Charaxinae. The presence of pasture best explains the abundance of all groups except Charaxinae, which was best explained by early-regrowth forest. The abundance of different species and groups are correlated with different kinds of vegetation cover. However, we demonstrate that small scales (100-200 m) are more effective at explaining the abundance of most butterflies. These results strongly suggest that efforts to preserve insect diversity in forest fragments should take in account the immediate surroundings of the fragment, and not only the regional landscape as a whole. In general, actions of people living near forest fragments are as important to fruit-feeding butterflies as large scale actions are, with the former being seldom specified in management plans or conservation policies. © 2012 Springer Science+Business Media B.V.
Keywords: Atlantic forest; Bioindicators; Brazil; Butterfly conservation; Forest fragmentation; Nymphalidae